Chemical Synthesis and Immunological Evaluation of a Pentasaccharide Bearing Multiple Rare Sugars as a Potential Anti‐pertussis Vaccine. (25th February 2020) - Wang, Peng; Huo, Chang‐xin; Lang, Shuyao; Caution, Kyle; Nick, Setare Tahmasebi; Dubey, Purnima; Deora, Rajendar; Huang, Xuefei
Abstract: With the infection rate of Bordetella pertussis at a 60‐year high, there is an urgent need for new anti‐pertussis vaccines. The lipopolysaccharide (LPS) of B. pertussis is an attractive antigen for vaccine development. With the presence of multiple rare sugars and unusual glycosyl linkages, the B. pertussis LPS is a highly challenging synthetic target. In this work, aided by molecular dynamics simulation and modeling, a pertussis‐LPS‐like pentasaccharide was chemically synthesized for the first time. The pentasaccharide was conjugated with a powerful carrier, bacteriophage Qβ, as a vaccine candidate. Immunization of mice with the conjugate induced robust anti‐glycan IgG responses with IgG titers reaching several million enzyme‐linked immunosorbent assay (ELISA) units. The antibodies generated were long lasting and boostable and could recognize multiple clinical strains of B. pertussis, highlighting the potential of Qβ‐glycan as a new anti‐pertussis vaccine. Abstract : Gib mir fünf ! Ein dem Pertussis‐Liposaccharid (LPS) ähnelndes Pentasaccharid mit mehreren ungewöhnlichen Zucker‐Untereinheiten wurde mit hoher Stereoselektivität und Gesamtausbeute synthetisiert. Konjugation des Pentasaccharids mit dem Trägerprotein Qβ ergibt einen potentiellen Impfstoff, der anti‐LPS‐Antikörper mit einer Breitbanderkennung gegenüber B .‐ pertussis ‐Stämmen erzeugt.